The Influence of Learning Models Teaching Game for Understanding (TGfu) on Critical Thinking Skills Students in Basketball Games - Dian Kardiansah; Ayi Suherman; Anggi Setia Lengkana (UNIB Press, 2024)
The purpose of this study is to ascertain : (1) the significant influence of the Teaching Games for Understanding (TGfU) learning model in basketball games on students critical thinking skills, (2) the significant influence of the Direct Instruction (DI) learning model in basketball games on students' critical thinking skills, (3) the significant difference in the influence between the Teaching Games for Understanding (TGfU) learning model and the Direct Instruction (DI) learning model in basketball games on students' critical thinking skills. This type of research is quasi-experimental design using randomized pretest-posttest group design. The population in this study is all seventh-grade classes of SMP Negeri 1 Rancaekek, Rancaekek District, Bandung Regency, West Java Province, totaling 11 classes with 543 students. The sampling technique used is cluster random sampling. The data analysis technique used is a significance test at the 5% level. The results of the study show that: (1) There is a significant influence of the Teaching Games For Understanding (TGfU) Learning Models on Students' Critical Thinking Skills in Basketball Games with a p-value (0.001) < (0.05). (2) The significant influence of the Direct Instruction (DI) learning model in basketball games on students' critical thinking skills with a p-value (0.001) < (0.05). (3) There is a significant difference between the Teaching Games For Understanding (TGfU) and Direct Instruction (DI) learning models on Students' Critical Thinking Skills in Basketball Games with a p-value (0.001) < (0.05).